Impact of climate services on Senegal's farmers - Hansen, James; Dinh, Dannie (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
Climate services involve the “production, translation, transfer, and use of climate knowledge and information in climate-informed decision making and climate-smart policy and planning.” 1 A well-functioning climate service provides the information and support that decisionmakers need to understand, anticipate, and manage climate-related risks. While climate services encompass a range of time scales, services for farmers emphasize information at weather (e.g., daily observations, forecasts out to about 10 days) and seasonal climate variability (e.g., historical seasonality, variability and trends; seasonal forecasts) time scales.